Does democratization Benefit the Environment in the long-run in the presence of inequality? - Thomas Drosdowski (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
Political Economy may provide an important link between inequality and pollution. This paper studies the dynamic relationship between inequality and redistributive policy leading to differing transitional paths of pollution to the steady state, using a pollution-augmented framework developed by Bénabou and employing numerical simulations. The result indicate that democratisation can be beneficial for the environment in the long run if the share of redistributive transfers devoted to abatement is relatively high. Otherwise, less wealth-biased and more democratic regimes display highest income and pollution levels, differing in transitional path contingent on initial inequality levels. Sustainable developement, defined as non-declining level of utility over time, is achived for a high degree of democracy when initial inequality is low. The representative agent with average wealth does not provide sustainability, which emphasizes the importance of heterogeneity in power and income for sustainability debates.
Keywords: Q5; D72; D31; 330; Pollution; Political Economy; Sustainability